Ketokohan dan Pemikiran Dakwah Tuan Haji Yusof Rawa (1922 – 2000) di Malaysia - Badlihisham Mohd Nasir; Abdur Razzaq (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2020)
Abstract: Article with the title 'Characteristics and Thought of Mr. Haji Yusof Rawa's Da'wah (1922 - 2000) in Malaysia', this aims to describe and analyze the character and thoughts of al-marhum Mr. Haji Yusof Rawa in the field of Islamic da'wah. It starts by highlighting his background in figures and goes on to talk about his Islamic da'wah thoughts. The method used in this study uses a library research method or approach. Literature study can be interpreted as a series of activities relating to the method of collecting library data, reading and recording and processing research material. The findings of this study indicate the role of this figure in controlling the age of the old order transition to the new order has been in line with the demands of the era. He succeeded in becoming a father to the party and upholding the fundamental principles that became the basis and compass for the next party journey. Although he sparked ideas and thoughts that symbolized the openness of PAS to the changing times, he was very wise in outlining the idealism of the party to the point of eternity until now. His strong stance in sparking Da'wah thoughts that were more similar to PAS-centric and shrouded in controversy at the time, had preceded many parties in introducing great ideas such as the Hadith tajdid which later was recognized as a source of inspiration for the hadhari Islamic ideas launched by the UMNO government led by Tun Abdullah Ahmad Badawi Keywords: Da’wah thought, Haji Yusof Rawa Abstrak: Artikel dengan judul ‘Ketokohan dan Pemikiran Dakwah Tuan Haji Yusof Rawa (1922 – 2000) di Malaysia’, ini bertujuan memaparkan dan menganalisis ketokohan dan pemikiran al-marhum Tuan Haji Yusof Rawa dalam bidang dakwah Islamiah. Dimulai dengan menyorot latar belakang ketokohan beliau dan seterusnya membincangkan mengenai pemikiran dakwah Islamiahnya. Metode yang digunakan dalam kajian ini menggunakan metode atau pendekatan kepustakaan (library research). Studi pustaka dapat diartikan sebagai serangkaian kegiatan yang berkenaan dengan metode pengumpulan data pustaka, membaca dan mencatat serta mengolah bahan penelitian. Temuan dari penelitian ini menunjukkan peranan tokoh ini dalam mengendalikan zaman transisi orde lama kepada orde baru telah sejalan dengan tuntutan zaman. Beliau berhasil menjadi seorang bapak bagi partai dan menegakkan asas fundamental yang menjadi dasar dan kompas kepada perjalanan partai selanjutnya. Walaupun beliau mencetuskan berbagai ide dan pemikiran yang melambangkan keterbukaan PAS kepada perubahan zaman, beliau sangat arif menggariskan idealisme partai hingga kekal utuh sampai sekarang. Ketokohannya dalam mencetuskan pemikiran dakwah yang lebih mirip kepada PAS-centric serta diselubungi dengan kontroversi pada waktu itu, telah mendahului banyak pihak dalam memperkenalkan gagasan besar seperti tajdid hadhari yang kemudian diakui menjadi sumber inspirasi kepada gagasan Islam hadhari yang dilancarkan oleh pemerintahan UMNO pimpinan Tun Abdullah Ahmad Badawi. Kata kunci: Pemikiran dakwah, Haji Yuso Rawa